The use of pepperlav aroma therapy (peppermint and lavender) as a natural approach to alleviate nausea and vomiting in pregnancy - juliastuti juliastuti (Institute of Computer Science (IOCS), 2023)
This systematic review aims to evaluate the use of Pepperlav aroma therapy, which combines peppermint and lavender essential oils, as a natural approach to alleviate nausea and vomiting in pregnancy. A comprehensive literature search was conducted using electronic databases to identify relevant studies. Studies evaluating the effectiveness of Pepperlav aroma therapy in reducing nausea and vomiting during pregnancy were included. Data extraction and quality assessment were performed, and the findings were synthesized narratively. Several studies were included in the review. The findings suggest that Pepperlav aroma therapy significantly reduces the frequency and intensity of nausea and vomiting in pregnant women. The combination of peppermint and lavender oils, known for their relaxing and antiemetic properties, appears to contribute to the therapeutic effects. However, further research is needed to validate these findings, elucidate the underlying mechanisms, evaluate long-term effects and safety, compare with other treatment modalities, and investigate individual factors influencing the response to Pepperlav aroma therapy. The use of Pepperlav aroma therapy shows promising results as a natural approach to alleviate nausea and vomiting in pregnancy. The relaxing and antiemetic properties of peppermint and lavender oils make them potential beneficial agents. However, further research is warranted to validate and confirm these findings, as well as to understand the mechanisms involved. It is crucial to consult with healthcare professionals or aromatherapy experts before implementing Pepperlav aroma therapy in pregnant women.